Population pharmacokinetic/pharmacodynamic joint modeling of ixazomib efficacy and safety using data from the pivotal phase III TOURMALINE‐MM1 study in multiple myeloma patients - Jaydeep K. Srimani; Paul M. Diderichsen; Michael J. Hanley; Karthik Venkatakrishnan; Richard Labotka; Neeraj Gupta (Wiley, 2022)
Abstract Ixazomib is an oral proteasome inhibitor approved in combination with lenalidomide and dexamethasone for the treatment of relapsed/refractory multiple myeloma (MM). Approval in the United States, Europe, and additional countries was based on results from the phase III TOURMALINE‐MM1 (C16010) study. Here, joint population pharmacokinetic/pharmacodynamic time‐to‐event (TTE) and discrete time Markov models were developed to describe key safety (rash and diarrhea events, and platelet counts) and efficacy (myeloma protein [M‐protein] and progression‐free survival [PFS]) outcomes observed in TOURMALINE‐MM1. Models reliably described observed safety and efficacy results; prior immunomodulatory drug therapy and race were significant covariates for diarrhea and rash events, respectively, whereas M‐protein dynamics were sufficiently characterized using TTE models of relapse and dropout. Moreover, baseline M‐protein was identified as a significant covariate for observed PFS. The developed framework represents an integrated approach to describing safety and efficacy with MM therapy, enabling the simulation of prospective trials and potential alternate dosing regimens.